Mahārashṭra Santaśiromaṇi Śrīekanātha Mahārāja yāñcẽ caritra : ākhyāyikā, kāvyanirikshaṇa, va utkrshṭa vẽce - Ājag̃āvakara, Jagannātha Raghunātha, 1879-1955 (SAMP early 20th-century Indian books project, 1926)
On the life and works of Ekanātha, ca. 1548-ca. 1600, Marathi saint poet.